Climate-resilience-oriented transformations of housing policy: strategic impulses from a multi-level real-world lab in the Ruhr. Issue 2 (1st March 2022) - Fuchs, Marisa; Klee, Kristina; Huning, Sandra; Szypulski, Anja
Abstract : In response to the climate emergency declared in many German cities in 2019, political decision makers, planners and researchers began promoting climate resilience in policy areas such as housing. This article discusses the potential impact and implementation of housing-market monitoring and housing action plans on analytical and strategic capacities at local and regional levels by presenting findings from a transdisciplinary, multi-level real-world laboratory in the Ruhr city region in Germany. It proposes an integrated multi-level approach to raise awareness and provide an accessible database for housing policies in climate-resilient city regions across administrative levels and sectoral borders.